The Effect of Green Marketing on Brand Purchase Intention & Green Consumerism - Ratih Pandu Mustikasari; Dian Hutami Rahmawati (Jurnal Spektrum Komunikasi, 2023)
Every citizen has the right to the opportunity to improve lifelong education. There are 3 forms of education namely formal education, non-formal education, and informal education. One form of non-formal education is the Center for Community Learning Activities (PKBM). Currently, it is estimated that there are as many as 14,500 registered PKBM. There is a need for a strong brand identity so that PKBM can continue to exist and become an option in society. This research focuses on building brand identity of PKBM as a non-formal educational institution that focuses on approaches in aspects of brand personality and aspects of internal and external relations of the institution. This study used qualitative research methods. The result of this study is that the brand personality built by PKBM Mentari is highlighted from non-formal learning methods with the addition of soft skills outside the classroom. PKBM Mentari is also trying to break the stereotype that PKBM is not a school of choice, by implementing study hours and the national curriculum. Brand personality is also shown from the contribution of learning citizens in community service. In the relationship aspect, PKBM development is based on a personal approach by being present as a solution to the problems of learning residents. The aspect of the relationship in building brand identity is formed from internal or institutional factors between the director and the tutor and external factors between the director, tutor, learning residents and the surrounding community.